Numerical Optimization and Noise Analysis of High-Tip-Speed Wind Turbine (Advances in Applied Mathematics and Mechanics, 2021)
With lower turbulence and less rigorous restrictions on noise levels, offshorewind farms provide favourable conditions for the development of high-tip-speed windturbines. In this study, the multi-objective optimization is presented for a 5MW windturbine design and the effects of high tip speed on power output, cost and noise areanalysed. In order to improve the convergence and efficiency of optimization, a noveltype of gradient-based multi-objective evolutionary algorithm is proposed based on uniformdecomposition and differential evolution. Optimization examples of the windturbines indicate that the new algorithm can obtain uniformly distributed optimal solutionsand this algorithm outperforms the conventional evolutionary algorithms inconvergence and optimization efficiency. For the 5MW wind turbines designed, increasingthe tip speed can greatly reduce the cost of energy (COE). When the tip speedincreases from 80m/s to 100m/s, under the same annual energy production, the COEdecreases by 3.2% in a class I wind farm and by 5.1% in a class III one, respectively,while the sound pressure level increases by a maximum of 4.4dB with the class IIIwind farm case.